2021
DOI: 10.1002/adfm.202110087
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Synthesis of Bismuth Nanoclusters within Carbon Nano‐Bundles from Metal–Organic Framework for Chloride‐Driven Electrochemical Deionization

Abstract: Ultrasmall metal nanoclusters (MNCs, <3 nm) have emerged as a novel class of functional nanomaterials. Different from the prosperous development of noble MNCs, the fabrication of non‐noble MNCs remains a major challenge, which greatly curtails the advance of relevant application fields. Herein the authors put forward an in situ synthesis strategy of bismuth nanoclusters (Bi NCs) within carbon nano‐bundles (Bi NCs@CNBs) by simply carbonizing the Bi‐containing metal–organic framework (Bi‐MOF), and deploy it as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 63 publications
(29 reference statements)
1
29
0
Order By: Relevance
“…[27][28][29] The modifiable pore characteristics endow MOFs with excellent function via encapsulation of various guest molecules such as quantum dots, nanoparticles, polyoxometalates, and polymers. [30][31][32][33][34][35][36][37] The resultant MOF composites often achieve better performance than individual components. Although many recent studies of host-guest hybrid MOFs for whitelight emission have been reported, [38][39][40][41][42][43][44] the intrinsic parameters such as the quantum yield, color-rendering index (CRI), especially for bicolor complementary WLE phosphors, still need to be improved.…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29] The modifiable pore characteristics endow MOFs with excellent function via encapsulation of various guest molecules such as quantum dots, nanoparticles, polyoxometalates, and polymers. [30][31][32][33][34][35][36][37] The resultant MOF composites often achieve better performance than individual components. Although many recent studies of host-guest hybrid MOFs for whitelight emission have been reported, [38][39][40][41][42][43][44] the intrinsic parameters such as the quantum yield, color-rendering index (CRI), especially for bicolor complementary WLE phosphors, still need to be improved.…”
Section: Introductionmentioning
confidence: 99%
“…The material had excellent stability over 30 cycles, in which only 9.4% reduction in SAC was observed. Liu, Wang, Yao, et al (2021) synthesized bismuth nanoclusters (Bi NCs) in carbon nano-bundles (Bi NCs@CNBs) by carbonizing the Bi containing metal-organic framework (Bi-MOF) and employed the same material as Cl À capturing electrode. The Bi-MOF provides better electronic conductivity and structural stability, exhibiting ASAR of 0.52 mg/g/s with better cycling stability.…”
Section: Rocking Chair Desalination (Rcd)mentioning
confidence: 99%
“…12−14 Among them, bismuth (Bi)-based compounds have emerged as promising active materials for a variety of catalysis applications due to their earth abundance, low cost, and less toxicity. 15 activity. 18 Consequently, carbon substrates are introduced to support Bi nanoparticles for catalytic 4-NP conversion.…”
Section: ■ Introductionmentioning
confidence: 98%
“…Unlike magnetic metals such as iron, cobalt, and nickel, which are prone to aggregation, nonmagnetic transition metals are more suitable for stable and long-term catalysis. Among them, bismuth (Bi)-based compounds have emerged as promising active materials for a variety of catalysis applications due to their earth abundance, low cost, and less toxicity. Several bismuth-based catalysts have been recently implemented for the catalytic reduction conversion of 4-NP. The semimetallic Bi nanoparticles were first demonstrated as a potential candidate for catalytic 4-NP reduction with a normalized rate constant of 27.51 s –1 g –1 ; however, their easy aggregation remarkably deteriorated the catalytic activity .…”
Section: Introductionmentioning
confidence: 99%